Modelling of Sustainable Blue Swimming Crab Supply Chain in East Java Using Soft System Methodology - Setyaningrum, Paramita; Gabriel, Azmi Alvian; Cholilie, Irvan Adhin (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
Abstract Blue swimming crab (Portunus pelagicus) is one of Indonesia's highest-export fishery commodities. Capture fisheries are dominated by fishermen with low productivity, efficiency, and income levels. There is a high-profit disparity between upstream and downstream actors, where fishermen get the lowest profit. This study aims to identify the causes of profit disparities between supply chain actors and propose a supply chain model to solve the profit disparity problem. The supply chain actors observed were fishermen, mini plants, processing companies, and exporters of blue swimming crab. Determining variables that affect profit gain based on the business activities of the supply chain actors of blue swimming crab was carried out. The conceptual model was made using the Soft System Methodology (SSM). The analysis result showed that the causes of profit disparity were the vast number of fishermen, lack of product value understanding, minimum capital and access to capital, awareness of fishing gear utilization, and the individual fisherman's work system. The conceptual model of the blue swimming crab supply chain proposed consists of the formation of fishing groups, coordination between fishing groups and Perum Perindo, collaborating with Pokja and fishing groups, and increasing collaboration between all supply chain actors of blue swimming crab.Keywords: blue swimming crab, fishermen, Soft System Methodology, supply chain Abstrak Rajungan (Portunus pelagicus) merupakan salah satu komoditas perikanan ekspor tertinggi di Indonesia. Usaha ikan tangkap didominasi oleh para nelayan dengan tingkat produktivitas, efisiensi, serta pendapatan yang rendah. Disparitas keuntungan yang tinggi terjadi antara pelaku rantai pasok dari hulu dan hilir. Nelayan memperoleh keuntungan paling rendah. Penelitian ini bertujuan mengidentifikasi penyebab disparitas keuntungan antara pelaku rantai pasok dan mengusulkan model rantai pasok sebagai solusi permasalahan disparitas keuntungan. Pelaku rantai pasok yang diamati adalah nelayan, mini plant, perusahaan pengolah rajungan, dan eksportir. Identifikasi variabel yang memengaruhi perolehan keuntungan berdasarkan aktivitas bisnis pelaku rantai pasok rajungan. Model konseptual dibuat menggunakan Soft System Methodology (SSM). Hasil analisis menunjukkan bahwa penyebab disparitas keuntungan adalah jumlah nelayan yang sangat banyak, pemahaman yang kurang terhadap nilai produk, modal dan akses permodalan yang minimum, kesadaran dalam penggunaan alat tangkap yang aman, dan sistem kerja nelayan yang masih dilaksanakan secara individu sehingga nelayan menerima keuntungan yang paling kecil di antara pelaku rantai pasok dari hulu dan hilir. Model konseptual rantai pasok rajungan yang diusulkan adalah pembentukan kelompok nelayan, koordinasi antara kelompok nelayan dan Perum Perindo, kolaborasi antara Pokja dan kelompok nelayan, dan meningkatkan kolaborasi antara seluruh pelaku rantai pasok rajungan.Kata kunci: nelayan, rajungan, rantai pasok, Soft System Methodology